Forming Ethical Resilience in Students in the Digital Age: Historical Experience and Leadership Practice - Rasulov Baxtiyor Maxmudjonovich (Goodwood Publishing, 2026)
Purpose: This study explores the formation of ethical resilience among students in the context of digital transformation. It integrates historical pedagogical values with modern leadership practices to identify strategies for protecting students from